2016
DOI: 10.1016/j.devcel.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB1/EphB3b Coordinate Bidirectional Epithelial-Mesenchymal Interactions Controlling Liver Morphogenesis and Laterality

Abstract: SummaryPositioning organs in the body often requires the movement of multiple tissues, yet the molecular and cellular mechanisms coordinating such movements are largely unknown. Here, we show that bidirectional signaling between EphrinB1 and EphB3b coordinates the movements of the hepatic endoderm and adjacent lateral plate mesoderm (LPM), resulting in asymmetric positioning of the zebrafish liver. EphrinB1 in hepatoblasts regulates directional migration and mediates interactions with the LPM, where EphB3b con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 49 publications
5
48
0
Order By: Relevance
“…Reporting in Developmental Cell , Cayuso et al (2016) demonstrate an active role of the endoderm in this process, challenging the prior view that the endoderm is passively pushed by the mesoderm. …”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Reporting in Developmental Cell , Cayuso et al (2016) demonstrate an active role of the endoderm in this process, challenging the prior view that the endoderm is passively pushed by the mesoderm. …”
mentioning
confidence: 60%
“…It has been shown that asymmetric movement of the mesoderm, acting through the extracellular matrix between the endoderm and mesoderm, pushes the endoderm tube towards one side of the developing embryo (Kurpios, et al, 2008; Horne-Badovinac, et al, 2003). In this issue of Developmental Cell , Cayuso et al (2016) reveal an active role for the endoderm in the positioning of the liver in zebrafish.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Elke Ober (DanStem, University of Copenhagen, Denmark) proposed a new mechanism of left−right asymmetry, in which repulsive cues between the endoderm and mesoderm position the developing liver (Cayuso et al, 2016), and Aaron Johnson (University of Colorado, Denver, CO) showed that multiple repulsive signals also direct myofibre morphogenesis (Williams et al, 2015). At the molecular level, Dan Fletcher (University of California, Berkeley, CA) presented evidence that protein exclusion at membrane interfaces can play an essential role in signalling and fusion at membrane interfaces (Schmid et al, 2016).…”
mentioning
confidence: 99%